Rootless Trees and Wingless Bees: An Exploration of Migrant Identity, Home, Nostalgia and Trauma in the Island of Missing Trees and the Beekeeper of Aleppo - CONTUK, ÜMİT (İstanbul Kültür Üniversitesi, 2024)
This study examines the interactions of identity, home, nostalgia, and trauma with the phenomenon of forced migration in Elif Shafak's The Island of Missing Trees (2021) and Christy Lefteri's The Beekeeper of Aleppo (2019). The issue of migration, which has always profoundly affected societies in history and which is still deeply felt today due to reasons such as proxy wars, civil unrest, the climate crisis, hunger, and poverty, has been approached from a holistic perspective by following the individual and inner journeys of the novel characters. The novels analyzed complement each other as they focus on different stages of the migration process. In this way, the analysis of the two novels has enabled the thesis to reveal commonalities in the areas analyzed while examining these differences simultaneously. As a result, this thesis concludes that migrant identities are fluid, changing, and multiple. It has been revealed that the concept of home, which is closely linked to identity, is one of the first casualties of migrants. It has been observed that the ambiguity in migrant identity is also valid for the concept of home. This thesis also discusses that home has a meaning that transcends physical materials such as walls and roofs and is a multi-layered concept that includes family members, family relationships, a sense of security, familiar objects, faces, sounds, and smells. It was also observed that nostalgia can have both a healing and a trapping effect on migrants. It has been recognized that the experience of migration, whether voluntary or forced, has various difficulties and that migrants carry these difficulties as a burden on their shoulders throughout their lives. As a result, the migrant has to cope with inner emptiness and incompleteness. In light of all this, it is emphasized that societies hosting refugees should also re-evaluate the issues discussed in this thesis with an introspective approach.
Köksüz Ağaçlar ve Kanatsız Arılar: Kayıp Ağaçlar Adası ve Halep Arıcısı'nda Göçmen Kı̇mlı̇ğı̇, Yuva, Nostaljı̇ ve Travma Üzerı̇ne Bı̇r İnceleme
Yüksek lisans tezi.
Keywords: Migration; Identity; Home; Nostalgia; Trauma; Migrant Experiences; The Island of Missing Trees; Elif Shafak; The Beekeeper of Aleppo; Christy Lefteri